On anti-Chudakov effect in ultrarelativistic electron-positron pair ionization loss in thin target - Trofymenko, S.V. (Вопросы атомной науки и техники, 2017)
The ionization loss of an ultrarelativistic e⁺e⁻ pair in a system of two separated targets { thick upstream, in which the pair is created, and thin downstream { is considered. The main attention is drawn to investigation of the effect of enhancement of the pair loss in thin target comparing to the sum of independent electron and positron losses (the one opposite to the Chudakov effect of pair ionization loss suppression). The problem is studied without the use of approximation of parallel electron and positron velocities which is usually applied for theoretical consideration of pair ionization loss. The dependence of the magnitude of the effect on the pair energy and its divergence angle is studied. The possibility of existence of such effect in the asymptotic case of large separations between the targets is shown. A simplified analytical expression describing the pair ionization loss dependence on distance between the targets under the conditions of manifestation of the discussed effect is obtained. Розглянуто іонізаційні втрати ультрарелятивістської e⁺e⁻ - пари в системі з двох мішеней - товстої, в якій пара народжується, і тонкої, - що розташовані одна за одною на певному проміжку. Основну увагу приділено дослідженню ефекта збільшення втрат пари в тонкій мішені порівняно з сумою незалежних втрат електрона і позитрона (який є протилежним до ефекту Чудакова зменшення іонізаційних втрат пари). Задачу розв'язано без використання наближення паралельних швидкостей електрона і позитрона, яке зазвичай застосовується при теоретичному розгляді іонізаційних втрат пар. Вивчено залежність величини даного ефекту від енергії і кута розльоту пари. Показана можливість існування такого ефекту в асимптотичному випадку при великих відстанях між мішенями. Отримано спрощений аналітичний вираз, що описує залежність іонізаційних втрат пари від відстані між мішенями в умовах прояву ефекту, що розглядається. Рассмотрены ионизационные потери ультрарелятивистской e⁺e⁻ - пары в системе из двух мишеней - толстой, в которой пара рождается, и тонкой - расположенных одна за другой на некотором промежутке. Основное внимание уделено исследованию эффекта увеличения потерь пары в тонкой мишени по сравнению с суммой независимых потерь электрона и позитрона (который является обратным эффекту Чудакова подавления ионизационных потерь пары). Задача решена без использования приближения параллельных скоростей электрона и позитрона, которое обычно применяется при теоретическом рассмотрении ионизационных потерь пар. Изучена зависимость величины данного эффекта от энергии и угла разлета пары. Показана возможность существования такого эффекта в асимптотическом случае при больших расстояниях между мишенями. Получено упрощенное аналитическое выражение, описывающее зависимость ионизационных потерь от расстояния между мишенями в условиях проявления рассматриваемого эффекта.